Política de formação continuada dos professores de educação física no estado de Pernambuco: avanços ou retrocessos? - Assis, Aniele Fernanda Silva de (2011)
This work constitutes a reflective inquiry about the policy for continuous training of teachers, and his dialogue between federal and state levels. We will review this policy at the national level and in programs of continuing education in physical education in Pernambuco, from the comparative analysis of two of their state administrations: that of 2003-2006 and 2007-2010. The poll has a reference to the historical and dialectical materialism and has the following instruments: a documentary survey and bibliography, and a questionnaire as a means of data collection. In the documentary survey, we take as normative references the following documents: the Law of Directives and Bases of Education - Law No. 9394/96, the National Education Plan - Law No. 10.172/01, Decree No. 6.755/09 establishing the National Policy on Teacher Training for Basic Education, the 2005 document establishing the National Network of Continuing Education, the Education Plan of the State of Pernambuco - Law No. 12252 of 08/07/2002; Programs Continuing Education for Physical Education in Pernambuco in 2003 and 2008. We conducted the literature review to provide us with references of other studies pertaining to this theme, focusing on the object of our study is the Policy of Continuing Education. And, in field research, we applied questionnaires with open and closed to teachers in Physical Education Exercise and belonging to state schools in Pernambuco. The theoretical discussion and analysis of documents and data collected show a legal system in relation to the policy of continuous training of teachers, but also indicate the need to align the concepts of continuing education in the legal documents contained in national and local level. However, we realize that the State Policy 2007-2010 advances in the management in relation to the previous administration, regarding the design, organization and product of continued training, even with the limits shown.